Engineered natural and synthetic polymer surfaces induce nuclear deformation in osteosarcoma cells. Issue 2 (16th April 2018) - Antmen, Ezgi; Ermis, Menekse; Demirci, Utkan; Hasirci, Vasif
Abstract: Cell‐substrate interactions involve constant probing of microenvironment by cells. One of the responses of cells to environmental cues is to change the conformation of their cytoplasm and nucleus. We hypothesized that surface chemistry and topography could be engineered to make these differences significant enough. When designing the substrates that would accentuate these differences, we prepared surfaces carrying cell adhesive biological cues arranged in specific patterns. Collagen type I and poly(lactic acid‐ co ‐glycolic acid) (PLGA) were used to represent substrates with biological cues and those without, and these materials were decorated with four square prism micropillars with different dimensions. The nuclear deformations were analyzed using some descriptors. Nucleus area and solidity were the best descriptors in distinguishing the substrates in terms of biological cues, while nucleus area, solidity, and circularity were more sensitive to the interpillar distances. Another distinguishing factor tested was the duration of contact. Nucleus area was the only descriptor sensitive to nuclear deformation change with time. PLGA was more suitable in nuclear conformation analysis while collagen was better in cell adhesion and proliferation. These deformations lead to changes in the molecular processes and further studies are needed to better understand cell mechanobiology. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 107B: 366–376, 2019.